Production and characterization of polyurethane castor oil (Ricinus communis) foam for nautical fender - Trovati, Graziella; Natali Suman, Marcos Vinicius [UNESP]; Sanches, Edgar Aparecido; Campelo, Pedro Henrique; Neto, Romeu Bessan; Neto, Salvador Claro; Trovati, Luiz Roberto [UNESP] (Elsevier, 2019)
Due to the fact that in South America old tires have been usually tied to vessels and convoys for the purpose of their lateral protection, this study was designed to address a contribution to the replacement of such material, since tires can affect the navigation safety. Therefore, the focus of this research was on the production and the mechanical properties evaluation of closed cells polyurethane foams, derived from castor oil (Ricinus communis), to be applied in the manufacture of nautical fenders. The polymer characterization was performed using thermal analysis, microstructural surface and mechanical techniques. The results showed that the main feature of the fenders is the proportional increase of reaction force and energy absorption, which promotes low pressure to the hull and mooring structures, maintaining their durability.
Keywords: Castor oil; Energy absorption; Fender; Polyurethane